The Influence of Competence and Training on Teacher Professionalism with Work Motivation as an Intervening Variable among Elementry School in Sumberejo Village (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Teacher professionalism in Sumberejo Village remains relatively low, as indicated by limited participation in training and weak motivation for continuous development. This study aimed to analyze the influence of competence and training on teacher professionalism, with work motivation as a mediating variable, using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research involved 36 elementary school teachers in Sumberejo Village, selected through a saturated sampling (census) technique. The findings reveal that competence and training have a significant positive influence on teacher professionalism, both directly and indirectly through work motivation. These results highlight the critical role of motivation as a mediator linking teacher competence and training with professional outcomes. The study provides context-specific insights for improving teacher development at the elementary level through competence-based training and motivation-oriented policies.